In vitro dry matter digestibility of selected forage sorghum silages as influenced by plant parts - Sonon, R.N. Jr.; Bolsen, K.K.; Brent, B.E.; Harbers, L.H.; Boyer, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eleven forage sorghum cultivars and one grain sorghum hybrid were used to determine the effect of individual plant parts on in vitro dry matter digestibility (IVDMD) of sorghum silage. IVDMD was highest for the head and lowest for the leaf sheath. When head and leaf blade parts were added to whole-plant material, IVDMD increased. When leaf sheath and stalk parts were added, IVDMD decreased, with the greatest decrease for leaf sheath. These results are consistent with an earlier study in our laboratory.
Keywords: Beef; Sorghum; Silage; Plant part; Digestibility